Microwave promoted solvent-free one-pot synthesis of N,N `-disubstituted urea derivatives - Jadhav, Vinod H.; Deshpande, S. S.; Borate, Hanumant B.; Wakharkar, R. D. (Journal of Chemical Research-S, 2005)
An efficient one-pot synthesis of N,N -disubstituted urea derivatives from substituted anilines, ethyl chloroformate and methyl anthranilate or methyl 3-amino-2-butenoate under microwave irradiation is reported.
Keywords: Anilines; methyl 3-amino-2-butenoate; methyl anthranilate; Microwave; urea derivatives

[Cu]-Catalyzed S(N)AR reactions: direct amination of electron deficient aryl halides with sodium azide and the synthesis of arylthioethers under Cu(II)-ascorbate redox system - Goriya, Yogesh; Ramana, C. V. (Tetrahedron, 2010)
A one pot [Cu]-promoted SNAr reaction of electron-deficient halobenzenes with sodium azide and the reduction of the intermediate aryl azides under the same Cu(II) ascorbate redox conditions leading to anilines has been documented. Control experiments revealed that both ascorbate and proline play important role in the reaction path way. Further, the use of this catalytic Cu(II) ascorbate redox system has been explored for the synthesis of arylthioethers. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Anilines; Azide reduction; Cu(II)-ascorbate redox system; SNAr reaction; Thioether

H-beta zeolite: an efficient, reusable catalyst for one-pot synthesis of isatins from anilines - Raj, I. Victor Paul; Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (Acta Chimica Slovenica, 2010)
We describe a simple and highly efficient procedure for the single-step preparation of isatins from the commercially available anilines using H-beta zeolite as a truly heterogeneous catalyst. H-beta zeolite is readily separated from reaction mixture by simple filtration and reused several times without considerable loss of activity.
Keywords: Anilines; H-beta zeolite; heterogeneous catalyst; isatins

Lithium tetrafluoroborate catalyzed highly efficient inter- and intramolecular aza-Michael addition with aromatic amines - Lad, Uday P.; Kulkarni, M. A.; Desai, Uday V.; Wadgaonkar, P. P. (Comptes Rendus Chimie, 2011)
Lithium tetrafluoroborate has been demonstrated for the first time to be an efficient catalyst in intermolecular aza-Michael addition aromatic amines to electron deficient alkenes. Suitability of the same catalyst in intramolecular aza-Michael addition leading 2-aryl-2,3-dihydroquinolin-4(1H) ones has also been described. (C) 2011 Published by Elsevier Masson SAS on behalf of Academie des sciences.
Keywords: 2-aryl-2; 3-dihydroquinolin-(4H)-1-ones; Anilines; Lithium tetrafluoroborate; Michael addition

Nickel-catalyzed N-vinylation of heteroaromatic amines via C-H bond activation - Landge, Vinod G.; Rana, Jagannath; Subaramanian, Murugan; Balaraman, Ekambaram (Organic & Biomolecular Chemistry, 2017)
Here, we report a ligand- and reductant-free nickel-catalyzed N-vinylation of heteroaromatic amines using biorenewable p-cymene as a solvent. This unprecedented cross-coupling strategy has high functional group tolerance (halides, alkoxy, cyano, chiral motif, etc.) and proceeded via C-H bond activation.
Keywords: Alkylation; Amination Reactions; Anilines; Aryl Chlorides; halides; Monoarylation; O Bonds; Precatalyst; Pyrimidines; Removeble Directing Group

Simple cobalt(II) chloride catalyzed N-alkylation of amines with alcohols - Midya, Siba P.; Mondal, Akash; Begum, Ayesha; Balaraman, Ekambaram (Synthesis-Stuttgart, 2017)
A facile cobalt-catalyzed N-alkylation of amines with alcohols using inexpensive, commercially available CoCl2 center dot 6H(2)O is reported. Employing this readily available cobalt catalyst, a variety of amines with wide functional group tolerance were selectively alkylated under benign conditions.
Keywords: (Hetero)Aromatic Amines; Alcohols; Amination; amines; Anilines; Aromatic-amines; Cobalt Catalysis; Dehydrogenation Borrowing Hydrogen; Efficient Catalysts; Hydrogen Autotransfer; Iridium; N-alkylation; Pincer-complex; Secondary Alcohols; Selective Alkylation